Adopting agroecological practices: Insights and impacts of the comprehensive homestead model in Mandla, Madhya Pradesh - Singh, Sonali; Gupta, Shweta; Alvi, Muzna (CGIAR System Organization, 2024)
Mandla district, located in Madhya Pradesh, India, is experiencing severe impacts of climate change that manifest in frequent droughts, extreme heat, and scanty rainfall. These conditions have led to significant agricultural challenges, including low crop productivity and widespread soil degradation (Census of India 2011 Madhya Pradesh, District Census Handbook Mandla. , 2011). The district’s smallholder farmers and tribal communities also face limited access to natural resources such as forests and water, which are essential for consumption and irrigation. These compounded challenges have exacerbated household food insecurity, often forcing families to migrate in search of better livelihoods. Addressing these issues requires a sustainable approach that integrates climate-resilient practices and promotes long-term agroecological sustainability.